Analisis Kinerja Keuangan BUMdes Di Kota Banda Aceh - Nurma Sari; Linda; Raida Fuadi (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
This study aims to analyze the effect of working capital, transparency accountability, community participation, and environmental turbulence on the financial performance of Village Owned Enterprises (BUMDes). The data used are primary data by distributing questionnaires to respondents consisting of 54 people. The sampling technique used a probability sample with simple random sampling. The research data was then processed using multiple regression analysis techniques aimed at knowing and analyzing the effect of exogenous variables either partially or simultaneously on endogenous variables. The results show that working capital, accountability, transparency, community participation, and turbulence together have a significant effect on financial performance, but not partially, there are only three of the five independent variables that have a significant positive effect on the financial performance of BUMDes, namely working capital, accountability and environmental turbulence with parameter coefficient values ​​that are not yet high. For this reason, it is necessary for BUMDes to provide open information in order to attract public interest to participate as well as support and evaluation from relevant agencies so that the performance of BUMDes is better.